2022
DOI: 10.1108/dlp-10-2021-0087
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of information literacy skills and knowledge-based competencies in using electronic resources among medical students

Abstract: Purpose This paper aims to focus on the information literacy skills and how the resources are being used by medical students of Mahatma Gandhi Medical College and Research Institute (MGMCRI), Pondicherry, India. The main aim is to determine the medical students use, purpose, search strategies and sources through which aware and literacy skills acquired. Further, this paper aims to bring out the problems faced. Design/methodology/approach A survey method was conducted through a structured questionnaire distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These findings were consistent with that of the previous studies reporting the positive relationship between information literacy and creativity [ 19 , 21–23 ]. Likewise, Chang and Hsu [ 60 ] also reported information literacy as a positive predictor of employees’ creativity. In addition, some other studies from the workplace context also had similar results [ 60–63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with that of the previous studies reporting the positive relationship between information literacy and creativity [ 19 , 21–23 ]. Likewise, Chang and Hsu [ 60 ] also reported information literacy as a positive predictor of employees’ creativity. In addition, some other studies from the workplace context also had similar results [ 60–63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Chang and Hsu [ 60 ] also reported information literacy as a positive predictor of employees’ creativity. In addition, some other studies from the workplace context also had similar results [ 60–63 ]. This finding also corroborated the outcomes of a recent and similar study by [ 16 ] who reported that digital literacy predicts positively creative thinking disposition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ever-growing electronic resources and databases, and abundant information choices in diverse format drastically changed the functioning of libraries and librarians (Anunobi and Udem, 2015; Feerrar, 2019; Senthur Selvi and Ganesan, 2021) and most of the services have been transformed from physical to online mode (Ayoku and Okafor, 2015). Moreover, it acts as a viable solution for the users to access from remote places (Ganesan and Gunasekaran, 2022). The other developments such as open-access resources, institutional repositories, social networks, digitization, and globalization, have changed the functioning of libraries across the world.…”
Section: Introductionmentioning
confidence: 99%